2009
DOI: 10.1007/s00209-009-0643-3
|View full text |Cite
|
Sign up to set email alerts
|

New HKT manifolds arising from quaternionic representations

Abstract: Abstract. We give a procedure for constructing an 8n-dimensional HKT Lie algebra starting from a 4n-dimensional one by using a quaternionic representation of the latter. The strong (respectively, weak, hyper-Kähler, balanced) condition is preserved by our construction. As an application of our results we obtain a new compact HKT manifold with holonomy in SL(n, H) which is not a nilmanifold. We find in addition new compact strong HKT manifolds.We also show that every Kähler Lie algebra equipped with a flat, tor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…dω r = 0 for any r = 1, 2, 3, then by Corollary 4 we get a strong HKT structure. An example in this case is given in [4,13].…”
Section: Corollarymentioning
confidence: 99%
See 2 more Smart Citations
“…dω r = 0 for any r = 1, 2, 3, then by Corollary 4 we get a strong HKT structure. An example in this case is given in [4,13].…”
Section: Corollarymentioning
confidence: 99%
“…for which the three Bismut connections associated to the three Hermitian structures (J r , h), r = 1, 2, 3, coincide. This geometry was introduced by Howe and Papadopoulos [21] and later studied for instance in [16,14,3,4,33]. Hyper-Hermitian connections with totally skew-symmetric torsion have applications in many branches of theoretical and mathematical physics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The strong condition is that a certain three-form is closed. Very few examples of such structures are known that are not hyperKähler: following work of Joyce [23], and building on Spindel et al [32], Grantcharov and Poon [16] showed that bi-invariant metrics on most compact groups of dimension 4n are strong ; Barberis and Fino [6] produced other compact examples; otherwise most known examples, including those in [14], are incomplete. We show that starting with a hyperKähler manifold with circle symmetry, harmonic functions again govern which twists are strong .…”
Section: Introductionmentioning
confidence: 99%
“…This connection is said to be an HKT-connection. This geometry is introduced in [25] and later studied for instance in [16,9,2,3,39]. A case of particular interest is when the torsion 3-form of such HKT-connection is closed.…”
Section: Introductionmentioning
confidence: 99%